Factors Influencing the Decision to Transform Bamboo into Products for the People of Houaphanh Province - SOULINTHONGTENG, Gia; Siphanthong, Bounthavy; SIOUDOMPHAN, Soutthavone (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This research aims to examine the current state of bamboo processing into commodities and analyze the factors influencing individuals' decisions to engage in bamboo processing in Huaphanh Province. A mixed-methods approach combining both quantitative and qualitative methods was employed. The target population consisted of individuals involved in bamboo processing within the province. Data were collected through questionnaires, and basic statistical methods were used to calculate averages and percentages. A multiple regression analysis using a Logit model was applied to determine the factors affecting decision-making. The findings indicate that most respondents consider bamboo processing their primary occupation and have been engaged in this activity for over ten years. Common products include kitchen utensils, personal items, and home decorations. Production is generally demand-driven, based on customer orders. Producers typically use personal funds and sell products directly from their homes. However, they face limitations in distributing products beyond their local areas and are unable to export to other provinces or abroad. The analysis identified four statistically significant factors influencing the decision to process bamboo into products: Processing potential – increased the likelihood of choosing bamboo processing by 137.8% (significant at the 0.1 level). Social factors – increased the likelihood by 22.7% (significant at the 0.01 level). Policy factors – increased the likelihood by 168.4% (significant at the 0.01 level). Technical factors – increased the likelihood by 199.4% (significant at the 0.05 level). These findings highlight the importance of supportive policies, social dynamics, technical capacity, and resource potential in promoting bamboo processing as a viable livelihood strategy in Huaphanh Province.